Map showing Indian agencies, and the number of and total areas of Indian reserves in the province of British Columbia
This is a map of British Columbia, probably from the 1920's, showing Indian agencies and number of and area of Indian reserves. "Exhibit C-170 (b)" Scale not given. Relief shown by spot heights. Shows Indian agencies as well as number of and area of Indian reserves. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .